Sport and exercise science. An introduction - Sewell, D. A.; Watkins, P.; Murray, G. (Hodder Education, 2012)
Sport and Exercise Science: An Introduction provides a broad-based foundation in the major areas that underpin the scientific study of sport and exercise science, thus helping undergraduate students to develop a sound understanding of human anatomy, physiology, nutrition, metabolism, biomechanics and psychology related to sport, exercise and health. It includes a range of useful features in every chapter, including clear explanations of key concepts, colour diagrams and photographs, activities and summaries to reinforce understanding, and on-line support materials for lecturers such as question and image banks. This is the essential companion text for any student studying sport and exercise science at degree level.